KEANEKARAGAMAN JENIS TUMBUHAN OBAT DI SEKITAR DANAU TAUJI NGATA KATUVUA DONGI - DONGI - Purnama, Rizky; Sudhartono, Arief; Rosyid, Abdul; Rukmi, Rukmi; Weraengkati, Yosua Wynalda (Institute of Computer Science (IOCS), 2024)
Diversity of medicinal plants in Indonesia around ± 1,040 species from seed plants. Now, the existing of many species of medicinal plants decrease. Traditional medicinal plants in Indonesia play a crucial role, particularly for those living in rural areas where access to healthcare facilities is still very limited. Dongi-dongi forest area has a variety of diversity of pls including medicinal plants. The purpose is knowing the diversity of medicinal plant species around Lake Tauji Ngata Katavua Dongi-dongi. This research has been conducted around 2 months starting from March to May 2023, using the exploratory survey by conducting a path transect. This method in which the observation follows the direction and location of the transect center line along the path of the research path which is paired with a discontinuous plot. The results showed 10 species including 104 individuals from 8 medicinal plants families, with the highest INP value is the Sintrong type (Crassocep halum Crepidiodes) with a value approximately 72.38% while the lowest INP value is the Legetan type (Acmella Oleraceae) with a value approximately 7.28%. Overall diversity index of medicinal plant species was found to be H' 2.21 included in the medium category.